Thermal stability from calorimetric measurements of multilayered NiFe specimens with different layer thickness. (August 2017) - Fiebig, J.; Jian, J.; Wang, H.; McCrea, J.; Lavernia, E.; Mukherjee, A.K.
Abstract: The thermal stability of multilayered NiFe specimens was investigated by using scanning differential calorimetry. Grain growth was found occurred at similar temperature, around 400 °C. Four different heating rates were selected and the activation energy was determined by using modified Kissinger analysis. The activation energy for grain growth is significantly higher than the activation energy for diffusion processes, in the bulks and grain boundaries that control grain growth. Graphical abstract: